Composition, abundance and distribution of macrozooplankton in Culebra Bay, Gulf of Papagayo, Pacific coast of Costa Rica and its value as bioindicator of pollution - Bednarski, Melinda (2004)
The abundance, distribution and composition of the macrozooplankton of Culebra Bay, Costa Rica (10º 38’ N - 85º 40’ W) were studied at four stations throughout the dry (February - May) and rainy (September-November) seasons of 2000. The samples were collected at two-week intervals using a 500μm mesh net with a 0.5 m diameter opening. Copepods (23-31%) and ostracods (20-34%) were predominant throughout the year, followed by cladocerans (2.5-14%), zoea (6.6-9.5%), and siphonophores (2.5-7.2%). High densities of zooplankton were obtained in February and March with peak abundance on March 18. The lowest densities were observed on September 3 and November 5. Significant differences in abundances at each station were observed for the groups Acartia tonsa (Copepoda), Ctenophora, Medusae, Ostracoda, Zoea, and Amphipoda. Comparison of the dry and rainy seasons revealed significantly higher zooplankton abundance in the dry season and copepod domination of all stations; during the rainy season ostracods dominated the off-shore areas. Zooplankton abundance and distribution are influenced by upwelling, which occurs during the dry season in Culebra Bay.